Blockchain technology, platforms and applications : a non-technical guide - Muhammad Arif Hamron (2017)
Blockchain has been around for quite some time, since 2009, but not many people know or have heard of this technology, and yet they have heard of Bitcoin. With financial institutions around the world collaborating and picking up on this technology, testing ways to integrate into their services and large investments being put into Blockchain startups, it speaks volume of how disruptive this technology is. What is Blockchain, and why is it gaining popularity? What are the essential ingredients that make up the Blockchain? This paper describes what a typical Blockchain is in a non-technical, high level manner to focus more on the understanding and appreciation of the technology. This is followed by the discussion of selected prominent Blockchain platforms which employ the Blockchain in their own way. Following that would be the applications which the Blockchain technology can be used for. This paper concludes with a summary of its contents and the future work of the Blockchain technology which can be explored to improve it.